Characteristics and outcome of early-onset, severe forms of Wiskott-Aldrich syndrome - Mahlaoui, Nizar; Pellier, Isabelle; Mignot, Cécile; Jais, Jean-Philippe; Bilhou-Nabéra, Chrystèle; Moshous, Despina; Neven, Bénédicte; Picard, Capucine; de Saint-Basile, Geneviève; Cavazzana-Calvo, Marina; Blanche, Stéphane; Fischer, Alain (Blood, 2013)
On the basis of a nationwide database of 160 patients with Wiskott-Aldrich syndrome (WAS), we identified a subset of infants who were significantly more likely to be attributed with an Ochs score of 5 before the age of 2 (n = 26 of 47 [55%], P = 2.8 × 10−7). A retrospective analysis revealed that these patients often had severe refractory thrombocytopenia (n = 13), autoimmune hemolytic anemia (n = 15), and vasculitis (n = 6). One patient had developed 2 distinct cancers. Hemizygous mutations predictive of the absence of WAS protein were identified in 19 of the 24 tested patients, and the absence of WAS protein was confirmed in all 10 investigated cases. Allogeneic hematopoietic stem cell transplantation (HSCT) was found to be a curative treatment with a relatively good prognosis because it was successful in 17 of 22 patients. Nevertheless, 3 patients experienced significant disease sequelae and 4 patients died before HSCT. Therefore, the present study identifies a distinct subgroup of WAS patients with early-onset, life-threatening manifestations. We suggest that HSCT is a curative strategy in this subgroup of patients and should be performed as early in life as possible, even when a fully matched donor is lacking. •This study identified a distinct subgroup of WAS patients with an early onset (before the age of 2 years) of severe, life-threatening manifestations.•HSCT is a curative strategy in this subgroup of patients and should be performed as early in life as possible, even when a fully matched donor is lacking.